The scientific case and the urgent need for a Prosocial Orthosociology - Koenraad Priels (University of Darussalam Gontor Press, 2023)
More and more scientific evidence shows that the primary source of societal harms and human suffering throughout history is rooted in the dominance of a Psychopathic Ruling Class. As we are witnessing the rise of a totalitarian, neo-fascist world order, there is an urgent need for a Prosocial Orthosociology: a holistic, critical, inter-and transdisciplinary, evidence based scientific research method to scrutinise all social structures from a human rights perspective. This evidence based holistic approach is aimed at exposing and eliminating anti-social, abusive, exploitative and harmful policies as an ethical imperative towards global justice and global health; with a primary focus on the Psychopathic Ruling Class, in order to address the very root problem